Prevalence and Determinants of True Thyroid Dysfunction Among Pediatric Referrals for Abnormal Thyroid Function Tests - Amit Lahoti MBBS; Jason Klein MD; Tiffany Schumaker DO; Patricia Vuguin MD; Graeme Frank MD (SAGE Publishing, 2016)
Background/Aims . Abnormalities in thyroid function tests (TFTs) are a common referral reason for pediatric endocrine evaluation. However, a sizable proportion of these laboratory abnormalities do not warrant therapy or endocrine follow-up. The objectives of this study were ( a ) to evaluate the prevalence of true thyroid dysfunction among pediatric endocrinology referrals for abnormal TFTs; ( b ) to identify the historical, clinical, and laboratory characteristics that predict decision to treat. Methods . This was a retrospective chart review of patients evaluated in pediatric endocrinology office during a weekly clinic designated for new referrals for abnormal TFTs in 2010. Results . A total of 230 patients were included in the study. Median age at referral was 12 years (range = 2-18); 56% were females. Routine screening was cited as the reason for performing TFTs by 33% patients. Majority was evaluated for hypothyroidism (n = 206). Elevated thyroid-stimulating hormone was the most common referral reason (n = 140). A total of 41 out of 206 patients were treated for hypothyroidism. Conclusions . Prevalence of hypothyroidism was 20%. Thyroid follow-up was not recommended for nearly one third of the patients. Among all the factors analyzed, an elevated thyroid-stimulating hormone level and antithyroglobulin antibodies strongly correlated with the decision to treat ( P < .005).